Sakrale Mahlzeiten in der Antike und das urchristliche Gemeindemahl - KOCH, Dietrich-Alex (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
In 1Cor 8‒10 Paul deals extensively with the problem of eating food sacrificed to idols, and in 1Cor 11:17‒34 he discusses abuses in the Lord's Supper in Corinth. In 1Cor 10:21 Paul contrasts the ‚table of the Lord‘ and the ‚table of the demons‘. Similarities and differences of these two forms of ritual table fellowship are discussed in this article starting with the archaeological evidence for ritual meals in antiquity.